Permian millipedes from the Fort Sill fissures of southwestern Oklahoma, with comments on allied taxa and millipedes preserved in karstic environments. (May 2021) - Hannibal, Joseph T.; May, William J.
Abstract: Permian millipedes are rare, especially so considering the relative abundance of millipedes in Carboniferous rocks. We report an early Permian millipede fauna containing three new genera and species of millipedes ( Oklahomasoma richardsspurense new genus new species, Karstiulus fortsillensis new genus new species, and Dolesea subtila new genus new species) found in fossil-producing pockets of the Fort Sill fissures exposed in the Dolese Quarry near Richards Spur, southwest Oklahoma, USA. These are the first new genera of invertebrates to be described from this site, one of the most prolific fossil-vertebrate sites in the world. We also comment on taxa with morphological similarities and note previously described occurrences of Permian millipedes as well as occurrences of fossil myriapods (millipedes and centipedes) in karst deposits (caves and fissure fills) in Europe, Africa, Asia, North America, and the Caribbean. In contrast with the forms found at Richards Spur, most of these previous accounts of millipedes found in caves and fissure fills are of Pleistocene forms that are closely allied to modern taxa. The taxa from Richards Spur bear some similarities to Pennsylvanian forms. Karst (cave and fissure) faunas should be ranked with concretion faunas, cannel coals, and amber faunas as a major source of fossil myriapods. UUID: http://zoobank.org/5d58e1fb-4e5b-4597-9cd9-5cc9e2096b4d